Removal of a Dental Implant Displaced into the Maxillary Sinus by Means of the Bone Lid Technique - Pietro Fusari; Matteo Doto; Matteo Chiapasco (Case Reports in Dentistry)
Background. Rehabilitation of edentulous jaws with implant-supported prosthesis has become a common practice among oral surgeons in the last three decades. This therapy presents a very low incidence of complications. One of them is the displacement of dental implants into the maxillary sinus. Dental implants, such as any other foreign body into the maxillary sinus, should be removed in order to prevent sinusitis. Methods. In this paper, we report a case of dental implant migrated in the maxillary sinus and removed by means of the bone lid technique. Results and Conclusion. The migration of dental implants into the maxillary sinus is rarely reported. Migrated implants should be considered for removal in order to prevent possible sinusal diseases. The implant has been removed without any complications, confirming the bone lid technique to be safe and reliable.